Analysis Of Income Of Mattress Entrepreneurs In Karaban Village, Karaban District, Pati District - Aprilia Retno Safitri; Didit Purnomo (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The aim of this research for reviewing mattres production businessman in Karaban Village Karaban Districts Pati. The reviewed were production capital, raw materials, labor, marketing, and income. The method is descriptive method. The population were 10 mattres businessman in Karaban Village Karaban Districts Pati. The data analyze is quantitative analyze with percentage table. The research result showed that the capital which was used by mattres businessman in Karaban Village Karaban Districts Pati each once mattres production was Rp5.000.000 until Rp24.000.000, the raw materials was come from Bandung and Tangerang, the labor amount is about 12 until 50 people, the result marketing of mattres production would be sell in Semarang, Kudus, Demak, Blora dan Grobogan. The mattres businessman income in Karaban Village Karaban Districts Pati is about Rp7.000.000 until Rp30.000.000.